Statistical monitoring of dust phenomenon in Khuzestan province with hourly approach - Parisa Ahadi; Shahriar Khaledi; Mahmoud Ahmadi (تحقیقات کاربردی علوم جغرافیایی)
Dust is referred to sediments of less than 100 microns in size which are transmitted as suspended particles. Dust storms are events which naturally occur in arid and semi-arid areas, especially in subtropical latitudes. One of the most known sources of dust is the west of Asia, including Arabian Peninsula, Syria, Iraq, and Iran, especially Khuzestan Province. The purpose of this study is to investigate the frequency and trend of dust phenomena on hourly, monthly, seasonal and annual scale between 1995 and 2015 in Khuzestan Province. The method in this study is based on statistical computation of dust parameters and also the trend analysis of data based on Mann-Kendall test and spatial distribution maps of dust phenomena. The results suggests that 78.57 percent of dust event are occurred between 9.30 am to 15.30 pm local time, concurrent with peak of sun radiation and earth surface warming, dryness of soil and local pressure difference. The hourly trend analysis is increasing and significant in all hours and the highest increase occurred at 9.30 pm to 12.30 pm.49 percent of dusty days occurred in June, July and May and also 73 percent of them are in spring and summer as following from temperature increase and water and soil resources drying in the province. The seasonal and annual spatial distribution of dust indicates that most of dusty days in all seasons are located in west of province which suggests dominance of external sources as the main source of dust and the importance of topography factor in this area.The Z value spatial analysis suggests high increase of dust event in recent 20 years in southeast, south and central areas of the province and also on last hours of day which demonstrator development of internal sources activities in increasing trend of dust event in recent decades.